2007
DOI: 10.1111/j.1365-3059.2006.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of tree xylem by Phytophthora ramorum, P. kernoviae and other Phytophthora species

Abstract: The aetiology and frequency of Phytophthora spp. in discoloured xylem tissue beneath phloem lesions was investigated in a range of broadleaved trees infected with P. ramorum, P. kernoviae, P. cambivora, P. citricola and other species. Isolation was attempted from the inner surface of 81 sterilized discoloured wood panels (6 × 4 cm) from 53 trees. Discolouration mostly extended 1-5 mm into the xylem (75%), but incursions of 6 -10 mm (10%) and 10 -25 mm (15%) were frequent. Of the wood panels, 81% yielded Phytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 19 publications
3
103
0
Order By: Relevance
“…Under favourable conditions some of these Clade 6 species, such as P. inundata, P. taxon PgChlamydo, P. gonapodyides and P. lacustris (e.g. Hansen and Delatour 1999;Greslebin et al 2005;Smith et al 2009;Randall 2011;Reeser et al 2011;Nechwatal et al 2012), can be aggressive tree pathogens (Brasier et al 2003b;Brown and Brasier 2007;Jung 2009). P. inundata has been isolated from dying native vegetation in Western Australia (WA) (Stukely et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Under favourable conditions some of these Clade 6 species, such as P. inundata, P. taxon PgChlamydo, P. gonapodyides and P. lacustris (e.g. Hansen and Delatour 1999;Greslebin et al 2005;Smith et al 2009;Randall 2011;Reeser et al 2011;Nechwatal et al 2012), can be aggressive tree pathogens (Brasier et al 2003b;Brown and Brasier 2007;Jung 2009). P. inundata has been isolated from dying native vegetation in Western Australia (WA) (Stukely et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Brown and Brasier (2007) reported survival of the pathogen in exposed wood of trees for up to 2 years.…”
Section: Shishkoff and Tooley (2004) Reported Survival Of P Ramorum mentioning
confidence: 99%
“…Discoloration was generally more extensive in the cambium and secondary phloem tissues than in the xylem; typically black discoloration extended less than 1 mm into xylem tissues, but was occasionally observed up to 3 cm into the xylem. Brown and Brasier (2007) found that P. ramorum commonly occupies xylem beneath phloem lesions, that the pathogen can penetrate xylem tissue, and that it spreads in xylem tissue ahead of phloem lesions. Parke and others (2007) demonstrated that the pathogen colonized tanoak sapwood, and then spread through xylem vessels.…”
Section: Colonization (Invasion)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some species of Phytophthora, like P. austrocedrae, P. cambivora, P. cinnamomi and P. ramorum among others can be found in the phloem, normally 4 associated with stem cankers (Hamm and Hansen 1987, Rizzo et al 2002, Brown and Brasier 2007, Parke et al 2007, Moralejo et al 2009, Greslebin and Hansen 2010. There are also a few Phytophthora species that have been detected in the xylem tissue.…”
Section: Introductionmentioning
confidence: 99%